The ruling of covering woman's feet during prayer – A jurisdiction comparative study – - Ramadan, Huda Muhammad (Journal of Islamic Sciences, 2020)
This research studies in a descriptive and analytical approach an old modern issue. In the past, scholars considered the ruling regarding covering the feet of women while praying. They differed on this issue each due to their time and circumstances. The point here is that the changes in woman's lifestyle including changes of fashion, mixing with men, leaving her home for long hours, all of which could cause woman to miss the prayers should she not perform them in the location where she is present. I have clarified in this research, in a comparative jurisdiction of the four Islamic schools of thought, the evidence and scholars' viewpoints including those approving the revealing of the foot and those opposing it. These viewpoints have been considered by scrutinizing their evidence including the authenticity of the evidence on the one hand, and the strength of the inference on the other hand. It has been concluded that each group of scholars have their own evidence on which they based their stance. In addition, it has been concluded that differences on this issue happened to exist within the same school of thought whereby some scholars gave priority for woman to reveal her feet while others gave priority to the apparent meanings of the text which do not approve revealing it. Having discussed the viewpoints and scrutinized their evidence and the weight of inference, the researcher has reached the conclusion that supports the extent of the weight of the majority who call for the necessity to cover the woman's two feet while performing prayers, as they are classified part of the woman's body.